Extraction and storage stability of a red colored dye from bignai (Antidesma bunius) - Del Pilar, Ma. Luisa P.
The red colored dye from bignai fruits was extracted and stored for two months under different conditions of pH and temperature to determine the optimum conditions for color retention during storage. Ethyl alcohol was used as the extracting solvent and the extract was concentrated by vacuum evaporation. The crude pigment concentrate was initially characterized in terms of its absorption spectrum in the visible range (400-700 mu) using spectrophotometric analysis. The wavelength of the maximum absorption (520 mu) was used to measure changes in pigment concentration during the storage studies. Results obtained in the storage stability studies indicated that the crude pigment concentrate from bignai retains its color longest at lower pH values, preferably at its natural pH of 3.15, and at freezing temperatures. However, the pigment is relatively stable also at refrigeration temperatures.